The simulation of triple exposure solar cookers / Mohd Fadhli Mat Zain - Mat Zain, Mohd Fadhli (2010)
Solar energy is the technology obtaining usable energy from the light of sun. Solar energy can be converted into other forms of energy, such as heat and electricity. NASA Solar Energy Panel identified three broad applications to be used from solar energy [1]the heating and cooling, [2] the chemical and biological conversion of organic materials to liquid, solid and gaseous fuels and [3]the generation of electricity.